Muslim politics in the Indo-Pakistan sub-continent, 1858-1916 - Chughtai, M (1960)
The decline of Muslim power in India became complete with the abolition of the sovereignty of the King of Delhi after the 1857 Mutiny. In the succeeding years far reaching changes took place in the economic and political condition of the Muslims. As is explained by Hunter in his Indian Musalmans, owing to the unfavourable educational and administrative policy of the Government, within fourteen years of the Mutiny the number of Muslims in Government departments and in respectable professions in Bengal had decreased to a negligible proportion. Conditions in other parts of the country were almost as depressing as in Bengal. The impoverishment of the Muslims had not wholly resulted from the events following the Mutiny. In fact, it had continued side by side with the decline of their power in India. The first reaction to this development appeared in the form of the Faraizi and the Wahhabi movements of the early nineteenth century. The Wahhabi movement, started by Sayyid Ahmad Barelvi, aimed at the re-establishment of Muslim rule in India by resorting to a holy war first against the Sikhs and after that against the British. He started the Jihad against the Sikhsin 1826 on the North-West Frontier and continued it with some success till 1831 when he was killed in a battle at Balakot. His followers appear to have remained active on the Frontier till the 1860s. The most influential Muslim in the post-Mutiny period was Sayyid Ahmad Khan. He believed that the Muslim regeneration in India was possible only after the establishment of cordial relations between them and their rulers. Both by his pen and word he endeavoured to prove that the Muslims were not disloyal to British rule. His efforts helped a great deal in bringing about a reconciliation between the Muslims and the British.